2010
DOI: 10.1111/j.1365-2893.2010.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the likelihood of sustained virological response in chronic hepatitis C therapy

Abstract: The likelihood of a sustained virological response (SVR) is the most important factor for physicians and patients in the decision to initiate and continue therapy for chronic hepatitis C (CHC) infection. This study identified predictive factors for SVR with peginterferon plus ribavirin (RBV) in patients with CHC treated under 'real-life' conditions. The study cohort consisted of patients from a large, retrospective German multicentre, observational study who had been treated with peginterferon alfa-2a plus RBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
4
11
1
Order By: Relevance
“…These results concur with those of previous large prospective studies of pegIFN-a/RBV therapy [17][18][19]. With regard to IL-6, as lower concentration of IL-6 at baseline in SVR was observed, IL-6 baseline level could serve as a predictive factor for SVR.…”
Section: Discussionsupporting
confidence: 93%
“…These results concur with those of previous large prospective studies of pegIFN-a/RBV therapy [17][18][19]. With regard to IL-6, as lower concentration of IL-6 at baseline in SVR was observed, IL-6 baseline level could serve as a predictive factor for SVR.…”
Section: Discussionsupporting
confidence: 93%
“…The rate of SVR in the current study was 50%, which is consistent with our previous data [30], as well as with the results obtained from clinical trials [12][13][14][15] and from "real life" clinical settings [31,32].…”
Section: Discussionsupporting
confidence: 81%
“…Baseline viral load was lower in our SVR group and it was higher in the relapsers, that observation showed statistical significance [14,15].…”
Section: Discussionsupporting
confidence: 54%
“…On the contrary, El Raziky [13] and her colleagues found significantly higher EVR and SVR in patients treated with peginterferon alpha 2a [13]. Furthermore, Mauss et al [14] in published a study to estimate the likelihood of achieving SVR and they found that if patients were matched by baseline characteristics, treatment with peginterferon alpha 2a may be a positive predictor of SVR when compared to peginterferon alpha 2b [14].…”
Section: Discussionmentioning
confidence: 96%